Exploring Endogenous Tryptamines: Overlooked Agents Against Fibrosis in Chronic Disease? A Narrative Review - Hunter W. Korsmo (Livers)
Long regarded as illicit substances with no clinical value, N-dimethylated tryptamines—such as N,N-dimethyltryptamine, 5-methoxy-N,N-dimethyltryptamine, and bufotenine—have been found to produce naturally in a wide variety of species, including humans. Known for their psychoactive effects through serotonin receptors (5-HTRs), N-dimethylated tryptamines are currently being reinvestigated clinically for their long-term benefits in mental disorders. Endogenous tryptamine is methylated by indolethylamine-N-methyltransferase (INMT), which can then serve as an agonist to pro-survival pathways, such as sigma non-opioid intracellular receptor 1 (SIGMAR1) signaling. Fibrogenic diseases, like metabolic-associated fatty liver disease (MAFLD), steatohepatitis (MASH), and chronic kidney disease (CKD) have shown changes in INMT and SIGMAR1 activity in the progression of disease pathogenesis. At the cellular level, endothelial cells and fibroblasts have been found to express INMT in various tissues; however, little is known about tryptamines in endothelial injury and fibrosis. In this review, I will give an overview of the biochemistry, molecular biology, and current evidence of INMT’s role in hepatic fibrogenesis. I will also discuss current pre-clinical and clinical findings of N-methylated tryptamines and highlight new and upcoming therapeutic strategies that may be adapted for mitigating fibrogenic diseases. Finally, I will mention recent findings for mutualistic gut bacteria influencing endogenous tryptamine signaling and metabolism.